Agronomic evaluation of Neonotonia wightii, Stylosanthes scabra and S. guianensis accessions in Ethiopia - Larbi, Asamoah; Ochang, J.; Hanson, Jean; Lazier, John R. (1992)
Presents the agronomic evaluation of 41 native Ethiopian Neonotonia wightii, 34 Stylosanthes scabra and 20 S. guianensis accessions carried out on an acid soil in southern Ethiopia under grazing. The accessions N. wightii ILCA 9794, 7764, 7892, S. scabra ILCA 12555, 11625, 11599, 11608 and S. guianensis ILCA 11737 and 11776 outyielded existing commercial cultivars. Recommended for further agronomic and animal evaluation.